2019
DOI: 10.1002/cpt.1558
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab Treatment Does Not Alter the Pharmacokinetics of the Cytochrome P450 3A4 Substrate Midazolam in Patients With Moderate to Severe Psoriasis

Abstract: This open-label disease-drug-drug interaction study assessed whether blockade of the interleukin (IL)-17A pathway by secukinumab and subsequent downregulation of inflammatory cytokines like IL-6 or high-sensitivity C-reactive protein affects the pharmacokinetics (PKs) of a sensitive probe substrate of the cytochrome P450 3A4 isoform (CYP3A4). The PKs of midazolam, metabolized by CYP3A4, was evaluated before and after 7 and 35 days of treatment initiation of subcutaneous secukinumab at a dose of 300 mg weekly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Accordingly, blockade of IL-4/IL-13 by dupilumab (Dupixent; Table 2) in patients with atopic dermatitis did not affect CYP activity to a clinically relevant extent 51 (Table 3). Similar results were obtained in patients with psoriasis, with the antipsoriatic IL-23 antagonists guselkumab (Tremfya), 52 risankizumab (Skyrizi), 53 or tildrakizumab (Ilumya), 54 or the IL-17A antagonists secukinumab (Cosentyx), 55 (Table 3) brodalumab (Siliq), or ixekizumab (Taltz) 7 . The findings from the studies with IL-23 inhibitors were also in line with absence of in vitro IL-23 effects on CYP enzyme expression.…”
Section: T a B L E 3 Continuedsupporting
confidence: 64%
“…Accordingly, blockade of IL-4/IL-13 by dupilumab (Dupixent; Table 2) in patients with atopic dermatitis did not affect CYP activity to a clinically relevant extent 51 (Table 3). Similar results were obtained in patients with psoriasis, with the antipsoriatic IL-23 antagonists guselkumab (Tremfya), 52 risankizumab (Skyrizi), 53 or tildrakizumab (Ilumya), 54 or the IL-17A antagonists secukinumab (Cosentyx), 55 (Table 3) brodalumab (Siliq), or ixekizumab (Taltz) 7 . The findings from the studies with IL-23 inhibitors were also in line with absence of in vitro IL-23 effects on CYP enzyme expression.…”
Section: T a B L E 3 Continuedsupporting
confidence: 64%
“…Indeed, these studies all showed that pharmacological inhibition of IL-6 restored CYP3A activity, with a significant decrease in simvastatin exposure of approximately 55 and 57% after the administration of sarilumab ( Lee, Daskalakis, et al, 2017 ) or tocilizumab ( Schmitt et al, 2011 ), respectively. Conversely, several other biotherapies targeting proinflammatory cytokines, such as TNF-ɑ ( Deng et al, 2018 ; Frye, Schneider, Frye, & Feldman, 2002 ), IL-17 ( Bruin et al, 2019 ), or IL-23 ( Khalilieh et al, 2018 ; Khatri et al, 2019 ) did not influence CYP activity. However, any effect of such biologics needs to be verified for various diseases with varying levels of proinflammatory cytokines, as the magnitude of these disease-dependent drug interactions are per se affected by the underlying disease.…”
Section: Pharmacological Consequences Of Inflammation-induced Metabolmentioning
confidence: 97%
“…These data suggest that blockade of the IL-6-dependent pathway reversed the suppression of CYP3A4 activity induced by inflammation and confirm the key role of IL-6 in the downregulation of CYP activity. Conversely, the antihuman IL-17A monoclonal antibody sekukinumab failed to modify the pharmacokinetic profile of midazolam in patients with moderate to severe psoriasis ( Bruin et al, 2019 ). Similarly, the antihuman IL-23 antibody risankizumab did not affect the in vivo activity of CYP1A2, CYP2C9, CYP2C19, CYP2D6, or CYP3A in patients with moderate plaque psoriasis ( Khatri et al, 2019 ).…”
Section: How To Integrate the Inflammatory Status In Personalized Medmentioning
confidence: 99%
“…Moreover, OKT3 (also known as muromonab, a CD3 receptor antibody) treatment transiently increased CyA through concentration, and authors suggested that OKT3 inhibits CYP3A4 metabolic activity by inducing transient cytokine release (Vasquez and Pollak, 1997). No changes were observed in drugs PK parameters before and after monoclonal antibodies administration, possibly because CYP metabolic activity was similar in psoriasis disease and in healthy volunteers (Bruin et al, 2019;Khatri et al, 2019). However, these therapies are used for a variety of diseases, with different levels of proinflammatory markers.…”
Section: Therapies With Immunomodulator Anti-tnf-α and -Mabsmentioning
confidence: 99%